2022
DOI: 10.3390/ani12182433
|View full text |Cite
|
Sign up to set email alerts
|

Factor Analysis of Genetic Parameters for Body Conformation Traits in Dual-Purpose Simmental Cattle

Abstract: In this study, we estimated the genetic parameters for 6 composite traits and 27 body conformation traits of 1016 dual-purpose Simmental cattle reared in northwestern China from 2010 to 2019 using a linear animal mixed model. To integrate these traits, a variety of methods were used as follows: (1) genetic parameters estimates for composite and individual body conformation traits based on the pedigree relationship matrix (A) and combined genomic-pedigree relationship matrix (H); (2) factor analysis to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Susanto et al (2018) reported phenotypic variation for claw angle at level 9.9% in Holstein dairy cows. Xu et al (2022) found a lower coefficient of variation in Simmental breed, ranging between 20.0% and 22.4%. Variability of the observed claw conformation traits could be affected by genetic effects, gene variation, environmental effects (herd, order of lactation, calving season), but also by the type of floor (Burgi et al, 2017), and individuality of evaluated animals (Canatan et al, 2021).…”
Section: Resultsmentioning
confidence: 80%
“…Susanto et al (2018) reported phenotypic variation for claw angle at level 9.9% in Holstein dairy cows. Xu et al (2022) found a lower coefficient of variation in Simmental breed, ranging between 20.0% and 22.4%. Variability of the observed claw conformation traits could be affected by genetic effects, gene variation, environmental effects (herd, order of lactation, calving season), but also by the type of floor (Burgi et al, 2017), and individuality of evaluated animals (Canatan et al, 2021).…”
Section: Resultsmentioning
confidence: 80%
“…It could be affected by the same factor as mentioned before. Next, the body depth is 72 -82 cm (ZAVADILOVÁ et al 2009) or 61 -90 cm (XU et al 2022). At the same time, the udder depth (UDD) has a reference distance of -19 to 22 cm (XU et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Next, the body depth is 72 -82 cm (ZAVADILOVÁ et al 2009) or 61 -90 cm (XU et al 2022). At the same time, the udder depth (UDD) has a reference distance of -19 to 22 cm (XU et al 2022). BDD and UDD traits are positioned on the standard interval data because the cattle breed sample between current exploration and references are similar.…”
Section: Resultsmentioning
confidence: 99%
“…RAN was genetically correlated with calving interval at −0.16 [27]. Extensive research on the genetic correlation between body conformation traits and somatic cell scores revealed the strongest associations with FUA, FTP, and UDE [28].…”
Section: Gwas Of Each Traitmentioning
confidence: 95%